The myth about Tsvetaeva in the epistolary of B. Pasternak - Хильская, Богдана Александровна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2017)
The author of this article refers to the writer's mythology, using the material of the epistolary dialogue of Boris Pasternak and Marina Tsvetaeva, since it gives the opportunity to consider the author's myth in the epistolary as an artistic space, provides a field for understanding the mythological phenomenon in mutually directed texts and gives clues to the analysis of the artistic thinking of the authors of the Silver Century.The aim of the work was to identify the constituent features of the myth about Tsvetaeva in the epistolary of Boris Pasternak, to elucidate the peculiarities of the semantic development of the author's myth as the main component of the written dialogue of poets. The article first analyzed the myth of Tsvetaeva in the epistolary of Pasternak, defined the nature of this myth, its place in the interpersonal and creative relationships of poets, its value as a way of understanding, knowing and accepting the Other.